Health Hazards, Hematological and Biochemical Alterations in Dry-Cleaning Workers using Perchloroethylene. - Marouf, Bushra Hassan (Iraqi Journal of Pharmaceutical Sciences, 2022)
Perchloroethylene (PERC) is commonly used as a dry-cleaning solvent, it is attributed to many deleterious effects in the biological system. The study aimed to investigate the harmful effect associated with PERC exposure among dry-cleaning workers. The study was carried out on 58 adults in two groups. PERC-exposed group; include thirty-two male dry-cleaning workers using PERC as a dry-cleaning solvent and twenty-six healthy non-exposed subjects. History of PERC exposure, use of personal protection equipment (PPE), safety measurement of the exposed group was recorded. Blood sample was taken from each participant for measurement of hematological markers, liver and kidney function tests. The results showed that 28.1% of the workers were using PPE regularly while 71.9% of the workers were not. Most of the workers 31(96.9%) were disposed of their waste products in improper way. Non-significant differences were observed in hematological indices between PERC-exposed group and non-exposed group. Serum level of kidney and liver function markers of the dry-cleaning workers were higher with statistically significant difference compared with the non-exposed group. In conclusion, a non-significant alteration in hematological parameters, while significant changes in part of liver and kidney functions indices have been demonstrated. Clinical observation indicated a harmful effect in PERC-exposed group.Key words: Occupational, PERC, personal protective equipment, dry cleaner